Potential Risk Factors for In-Hospital Mortality in Patients with Moderate-to-Severe Blunt Multiple Trauma Who Survive Initial Resuscitation - Yucel, Neslihan; Ozturk Demir, Tuba; Derya, Serdar; Oguzturk, Hakan; Bicakcioglu, Murat; Yetkin, Funda (Emergency Medicine International, 2018)
Introduction. The aim was to identify risk factors that influence in-hospital mortality for patients with moderate-to-severe blunt multiple trauma (BMT) who survive initial resuscitation. Methods. The prospective study involved 195 adult patients with BMT who were admitted to a referral hospital’s emergency department (ED) between May 1, 2015, and May 31, 2016. Results. Forty-three (22%) of the 195 patients died in hospital. Multivariate analysis identified low blood pH (odds ratio [OR] 6.580, 95% confidence interval [CI] 1.12-38.51), high serum lactate level (OR 1.041, 95% CI 1.01-1.07), high ISS (OR 1.109, 95% CI 1.06-1.16), high APACHE II score (OR 1.189, 95% CI 1.07-1.33), traumatic brain injury (TBI) (OR 4.358, 95% CI 0.76-24.86), severe hemorrhage (OR 5.314, 95% CI 1.07-26.49), and coagulopathy (OR 5.916, 95% CI 1.17-29.90) as useful predictors of acute in-hospital mortality. High ISS (OR 1.047, 95% CI 1.02-1.08), TBI (OR 8.922, 95% CI 2.57-31.00), sepsis (OR 4.956, 95% CI 1.99-12.36), acute respiratory distress syndrome (ARDS) (OR 8.036, 95% CI 1.85-34.84), respiratory failure (OR 9.630, 95% CI 2.64-35.14), renal failure (OR 74.803, 95% CI 11.34-493.43), and multiple organ failure [MOF] (OR 10.415, 95% CI 4.48-24.24) were risk factors for late in-hospital mortality. High Glasgow Coma Scale (GCS) was a good predictor for survival at 2, 7, and 28 or more days of hospitalization (OR 0.708 and 95% CI 0.56-0.09; OR 0.835 and 95% CI 0.73-0.95; OR 0.798 and 95% CI 0.71-0.90, resp.). Conclusion. Several factors signal poor short-term outcome for patients who present to the ED with moderate-to-severe BMT: low blood pH, high serum lactate level, presence of TBI, severe hemorrhage, coagulopathy, organ failure (respiratory, renal, and MOF), and ARDS. For this patient group, ISS and APACHE II scores might be helpful for stratifying by mortality risk, and GCS might be a good predictor for survival.